PENCIPTAAN FILM DOKUMENTER TARI TOGA DARI KERAJAAN DHARMASRAYA KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - ARFAH ARIANCE, Drs. Syafwan, M.Si, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Toga Dance is a scarce traditional art from Dhamasraya Kingdom whichcentered in Siguntur Dhamasraya Regency. However, the existence of this scarce traditional art still has not been known yet. It is important to know what Toga Dance is and its history in Dhamasraya Kingdom. A documentary movie is one of some effective medias because the information conveyed through the documentary movie is more interesting on getting audience target’s attention. The designing of this documentary movie is aimed to campaign a Toga Dance and Dhamasraya Kingdom, by using an expository approach which conveying information by explaining facts combining with pictures. The methodology used is opposite to some literatures, and it uses 5W+1H method by understanding all information on a case. So the choosing of campaign mediais more effective and the messages which are delivered can be understood by the audience target.The movie begins by showing a picture of Indonesian map, then a briefexplanations about Dhamasraya Kingdom, the origin of Toga Dance, thepresentation of Toga Dance, and last is the elements of Toga Dance. Instead of documentary movie, this campaign is accompanied by supporting medias such as calendar, banner, poster, T-shirt, CD label, CD cover, key chains, and thriller which aimed to strengthen the main media.Keywords: Campaign Media, Toga Dance, Documentary Movie